Prolog: The Next 50 Years - Warren, David S.; Dahl, Veronica; Eiter, Thomas; Hermenegildo, Manuel V.; Kowalski, Robert; Rossi, Francesca (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This volume was motivated by the Year of Prolog initiative, launched to celebrate the 50th anniversary of the emergence of Prolog through the work of Alain Colmerauer's team in Marseille. The volume editors, authors, and scientific advisors and reviewers have been the leading researchers and programmers in this field over decades, and the book represents an excellent overview of the field, its successes, and its future. After a first chapter that gently introduces the Prolog programming language using examples, the next 7 papers discuss general views of the language, possible extensions for the future, and how Prolog can generally be used to solve problems; the next 5 papers explore ideas and experiences of teaching Prolog programming and then 2 papers discuss technology that has been developed for help in that teaching; the next 3 papers describe new languages based on Prolog which show future directions for logic programming; the next 5 chapters explain the applications that were the finalists for the 2022 Alain Colmerauer Prize; and the final 8 papers describe applications developed using the Prolog language, demonstrating the language's range.
Background -- Introduction to Prolog -- About Prolog, present and future -- Types, modes and so much more - the Prolog way -- Manuel Carro Prolog as a Knowledge Representation Language -- Prolog: Past, Present, and Future -- Writing Correct Prolog Programs -- Demonstrating Multiple Prolog Programming Techniques through a Single Operation -- Logical Semantics for Prolog -- The Janus System: A Bridge to New Prolog Applications -- Teaching Prolog -- Some Thoughts on How to Teach Prolog -- Simultaneously Teaching Mathematics and Prolog in School Curricula: A Mutual Benefit -- Logic Programming at Elementary School: Why, what and how should we teach Logic Programming to children -- Prolog Education in Selected High Schools in Bulgaria -- Introducing Prolog in Language-Informed Ways -- Tools for teaching Prolog -- Teaching Prolog with Active Logic Documents -- Simply Logical - The First Three Decades -- Prolog-based languages and systems Dynamic Logic Programming -- Combining Prolog and Imperative Computing in LPS -- Quintero Ergo: A Quest for Declarativity in Logic Programming -- Prolog applications: finalists for the Colmerauer prize ProB: Harnessing the Power of Prolog to Bring Formal Models and Mathematics to Life -- Pacioli: a PROLOG system for financial report validation -- Logic Model Processing -- Symbium: Using logic programming to streamline citizen-to-government interactions -- PROLEG: Practical Legal Reasoning System -- Contributed Prolog applications -- Logical English for Law and Education -- Exploiting Logic Programming for Runtime Verification: Current and Future Perspectives -- Prolog meets Biology -- Prolog in Automated Reasoning in Geometry -- Logic-based Explainable and Incremental Machine Learning -- Reflections on Automation, Learnability and Expressiveness in Logic-based Programming Languages -- Prolog for Scientific Explanation -- Machines as Thought Partners: Reflections on 50 Years of Prolog.
Keywords: Artificial intelligence; Computer science; Artificial Intelligence; Computer Science Logic and Foundations of Programming